Pelayanan Pastoral Kontekstual sebagai Pendekatan Penginjilan di Desa Rantau Buda Kalimantan Selatan - H Harming; Ferderika Pertiwi Ndiy (Jurnal Teologi Praktika, 2020)
Contextual Pastoral Services as an Evangelical Approach in Rantau Buda Village in South Kalimantan, this article describes thte alternative proposals related to contextual pastoral servis to the community, in the framework of evangelical. Given the existence of a multicultural society in this context, namely in Rantau Buda, South Kalimantan. To explain the topic, the writer uses descriptive analysis method with a qualitative approach. Based on the results obtained, there are several important points made in contextusl pastoral care as am evangelistic approach, namely by praying and fasting, approaching the local government, cultural introduction, pastoral visitation.